A multiple defect approach to bridge life cycle modelling - Calvert, Gareth Samuel (2021)
Bridges are critical assets for the safe, reliable and functional operation of transportation networks. Infrastructure asset managers are responsible for ensuring that these bridges adhere to rigorous safety standards using the finite resources available to transportation agencies. Predicting future condition, forecasting required interventions and developing equitable resource allocations from limited budgets is a challenging task for bridge asset managers. To facilitate the decision making process at network level and to present decisions to stakeholders, it is common that a life cycle analysis is performed to evaluate the outcomes of different potential management strategies. An accurate bridge life cycle analysis is contingent on an appropriate bridge deterioration model being employed.